Increasing silicone mold longevity: a review of surface modification techniques for PDMS-PDMS double casting. Issue 4 (2nd October 2021) - Ansari, Ali; Trehan, Rajiv; Watson, Craig; Senyo, Samuel
ABSTRACT: Polydimethylsiloxane (PDMS) has been used extensively for microfluidic devices due to its chemical properties allowing for rapid molding and versatile biological application. Soft lithography-based PDMS fabrication primarily comprises casting from patterned photoresist on a silicon wafer. The patterned photoresist is often replaced with the cast PDMS as a more durable template mold for final PDMS fabrication that is less fragile and expensive. PDMS-PDMS double-casting prolongs the longevity of soft lithography molds and reduces overall costs to microfluidic applications. A common end to the lifetime of PDMS negative masters is the risk of bonding between the replicate and mold and distorted topographical features. This review examines common chemical and physical debonding approaches between PDMS-PDMS castings to extend the lifetime of PDMS masters.